THE INFLUENCE OF GREEN MARKETING MIX AND GREEN BRAND AWARENESS TOWARDS CONSUMER PURCHASE INTENTION AT STARBUCKS COFFEE MANADO - Gabriela Siwu; Willem J. F. A. Tumbuan; Lawren J. Rumokoy (Universitas Sam Ratulangi, 2023)
This research aims to determine the influence of green marketing mix and green brand awareness towards consumer purchase intention at Starbucks Coffee Manado. This study uses quantitative methods and multiple linear regression to assess the impact of product quality and price on customer satisfaction. The sample for this study was 100 respondents. The sampling technique is the purposive sampling method, and the data collection method is a questionnaire run through Google Form. Testing and data analysis in this study using SPSS 26 software. This study shows that the Green Marketing Mix (X1) has an effect on consumers' purchase intentions, but Green Brand Awareness (X2) has no effect on increasing consumers' purchase intentions. This implies that Starbucks coffee shops in Manado must continue to maintain and improve their green marketing mix and increase the green brand awareness of their brand for consumers, so that a competitive advantage will be achieved. Keywords: green marketing mix, green brand awareness, consumer purchase intention